Effective Market Access for Least Developed Countries’ Services Exports - United Nations Conference on Trade; Development (United Nations, 2020)
The LDC Waiver is a legal tool that enables WTO Members to sidestep their obligation to treat all services imports equally under the Most-Favoured Nation (MFN) clause through the granting preferential treatment to services and service exporters from a Least Developed Country (LDC). It is similar to the “Enabling Clause” for goods within the Generalized System of Preferences (GSP), except that the Waiver only benefits LDCs, not all developing countries. It operates thus as an “LDC-only Enabling Clause for services”. The Waiver only enables preferences, it does not require WTO Members to grant them, nor provide them with specific ideas or tools to facilitate LDCs’ exports into their markets. This paper presents the findings of the pilot study on Cambodia. Focusing on a selection of services sectors of particular export interest to Cambodia, this case-study assesses, where appropriate on an anecdotal basis, whether and to what extent the preferences granted by WTO Members respond to the market access, regulatory and other barriers experienced by Cambodia’s services exporters in their export market(s). By converging all available sources of information, the analysis aims to identify the relevance of the notified preferences for Cambodia’s services exports, possible gaps and opportunities for further development of improved market access mechanisms, as well as its utilization by LDCS’ services exporters.